Gestures of testimony : torture, trauma, and affect in literature - Richardson, Michael, 1980- (Bloomsbury Academic, an imprint of Bloomsbury Publishing Inc, 2016)
"After 9/11, the United States became a nation that sanctioned torture. Detainees across the globe were waterboarded, deprived of sleep, beaten by guards, blasted with deafening music and forced into obscene acts. Their torture presents a profound problem for literature: torturous pain and its traumatic aftermath have long been held to destroy language, shatter experience, and refuse representation. Challenging accepted thinking, Gestures of Testimony: Torture, Trauma, and Affect in Literature asks how literature might bear witness to the tortures of a war waged against fear itself. Bringing the vibrant field of affect theory to bear on theories of torture and power, Richardson adopts an interdisciplinary approach to show how testimony founded in affect can bear witness to torture and its traumas. Grounded in provocative readings of fiction by George Orwell, Franz Kafka, Arthur Koestler, Anne Michaels and Janette Turner Hospital, poems by Guantanamo detainees, memoirs of interrogators and detainees, contemporary films, and the Torture Memos of the Bush Administration, the analysis traverses politics, law and cinema to re-think literary testimony. Drawing upon some of the most influential thinkers of recent times on power, affect, trauma and torture, the book does more than critique culture and literature: it proposes new practices of literary witnessing. Gestures of Testimony gives shape to a mode of gestural testimony, a reaching beyond the page in the writing of torture in fiction that reveals the shape, depth and intensity of violent trauma-even as it embodies its veiling."--